Genome‐wide Association Study of Agronomic Traits in a Spring‐Planted North American Elite Hard Red Spring Wheat Panel. Issue 5 (12th July 2018) - Godoy, Jayfred; Gizaw, Shiferaw; Chao, Shiaoman; Blake, Nancy; Carter, Arron; Cuthbert, Richard; Dubcovsky, Jorge; Hucl, Pierre; Kephart, Ken; Pozniak, Curtis; Prasad, P.V. Vara; Pumphrey, Michael; et al.
Abstract : Inbred cultivars and advanced breeding lines have been subjected to numerous recombination cycles, have strong allelic selection for desired traits, and share important attributes for adaptation and agronomic performance. Genetic variation in elite gene pools captured using molecular markers is immediately useful for cultivar development. The primary goal of this study was to implement a genome‐wide association study for 17 agronomic traits using elite inbred lines. A panel consisting of 237 elite hard red spring wheat ( Triticum aestivum L.) lines from different wheat breeding institutions in North America were evaluated in 11 locations over 2 yr. A total of 19, 192 polymorphic single‐nucleotide polymorphism (SNP) markers from the Illumina 90K SNP array and markers linked to major genes controlling plant height, photoperiod sensitivity, and vernalization were used to assay the population. Linkage disequilibrium was observed to decay within a map distance of ∼3 cM in the A and B genomes and 7 cM in the D genome. A total of 226 marker‐trait associations were identified. Potentially novel associations were detected for grain yield on chromosome 2B and kernels per spike on 1B and 7D, whereas others colocalized with well‐known adaptation loci for photoperiod response, vernalization, and plant height. The frequency of positive alleles for specific marker‐trait associations differed among the programs, suggesting targets for introgression by the respective breeding programs.